Faktor-Faktor Yang Mempengaruhi Remaja Melakukan Tindakan Cyberbullying - Mayuni, Ni Putu Wida; Fridari, I Gusti Ayu Diah (Innovative: Journal Of Social Science Research, 2025)
Bullying is currently an action that is often carried out among teenagers, not only in real life but is often carried out through internet media which is called cyberbullying. This research aims to find out what factors encourage teenagers to commit cyberbullying. The method used is a literature review. Article search source via Google Scholar library sources with article publication between 2014-2023. The results of the literature review show that factors that influence teenagers to commit cyberbullying include personality type, self-esteem and loneliness, empathy ability, problematic internet use, conformity and emotional regulation, peer pressure, self-esteem and gender, internal and external motivation, intensity of use. Instagram, victim is a close friend, history of bullying, don't think about the victim.